Pemeriksaan Protein, Kolesterol dan Laktat Dehidrogenase Cairan Pleura sebagai Parameter dalam membedakan Efusi Pleura Transudat dan Eksudat - Ginting, Guntur Mulia Jendry; Abidin, Alwinsyah; Keliat, Ermanta Ngirim (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction To evaluate the benefit of three pleural fluid parameters pLDH, pProt and pChol both in single or combination form for differentiating exudative and transudative pleural effusion.Methods Sixty six cases of pleural effusion at Adam Malik Hospital from January-Mei 2014 were divided into exudate (56) and transudate group (10) based on their definite clinical diagnosis. Comparations were made between all parameters in single and combination form to evaluate its strength.Results All parameters both in single or combination were significantly different between exudate and transudate. However, the combination of two or more from three parameters (pLDH+pProt / pLDH+pChol / pProt+pChol / pLDH+pProt+pChol) were found superior in accuracy (92.4%), sensitivity (94.6%), and NPV (75%).Conclusion This study found that combination of two or more from three parameters (pLDH, pProt and pChol) has superiority in differentiating exudate and transudate pleural fluid.Keywords : Pleural effusion; transudat; exudate